Effect of Various Curing Regimes on Some Properties of Reactive Powder Concrete RPC (Journal of Engineering, 2024)
In the current study, the impacts of various curing states on some properties of reactive powder concrete (compressive strength, flexural strength, and dry bulk density) are being experimentally studied. The curing conditions include four different methods: immersion in normal water temperature (considered the reference curing state), immersion in warm water at 35ºC, immersion in boiling water, and curing with steam. For every combination, the water/binder ratio stayed unchanged at 0.2. Each reactive concrete mix was cast into three different configurations: 50mm only for cubes and 50×50×250 mm for prisms. Based on the improvement of RPC mechanical characteristics, the optimum curing method, as determined by the results, is immersion in warm water at 35ºC for all mixtures containing quartz powder of 20% by mass of cement and fly ash as a filler. The outcomes exhibited that using a warm water curing regime increased the RPC's compressive strength by 22.1%, flexural strength using 18.3% and dry density by 0.62% at 28 days following the comparison of the test grades to the reference curing regime.